Morphological ensembles of N-doped porous carbon derived from ZIF-8/Fe-graphene nanocomposites: processing and electrocatalytic studies - Thomas, Minju; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (ChemistrySelect, 2018)
Engineering the active site density of porous carbon catalysts for enhanced electrocatalytic activity is the current focus in the quest for economically viable fuel cells. Herein, we synthesise ZIF-8/Fe-graphene composites for the formation of N and Fe co-doped carbon with diverse morphologies ranging from tubes and sheets to frameworks of carbon. A synthetic strategy involving the one pot synthesis of ZIF-8 based composites is accomplished by the reaction of 2-methylimidazole with mixed Zn/Fe salt solution containing graphene dispersions. The high temperature heat treatment of this precursor mix yielded micro-meso porous architectures of N, Fe co-doped carbon with dispersions of Fe/Fe3C. An onset potential value of 0.95 V and a half-wave potential of 0.82 V coupled with excellent durability and stability in alkaline medium indicated improved electrocatalytic performances over its commercial Pt/C counterpart. The appreciable electrocatalytic properties of the synthesized carbon are attributed to its morphological diversity, hybrid structure, high N doping and its heteroporous characteristics. The dispersed Fe/Fe3C and FeNx sites facilitated enhanced oxygen adsorption and the graphene inclusions in the composite provided retention of high nitrogen contents.
Keywords: electrocatalyst; fuel cell; N- Fe co-doped carbon; oxygen reduction reaction; ZIF-8

Made to measure squaramide COF cathode for zinc dual-ion battery with enriched storage via redox electrolyte - Kushwaha, Rinku; Jain, Chitvan; Shekhar, Pragalbh; Rase, Deepak; Illathvalappil, Rajith; Mekan, Deep; Camellus, Augastus; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2023)
Aqueous rechargeable batteries are promising grid-scale energy storage devices because of their affordability, operational safety, and environmental benignity. Among these, Zn-ion batteries (ZIBs) have unfolded new horizons. Designing superior cathodes for ZIBs is crucial. Covalent organic frameworks (COFs) can be made redox active with a high storage surface. Here, for the first time, a chelating COF with redox-active ZnI2 in a ZnSO4(aq) electrolyte is combined. Including iodide harvests an approximately threefold enhancement in capacity from 208 to 690 mAh g(-1) at 1.5 A g(-1), the highest among all the COF-derived ZIBs. Remarkably, a charge-discharge curve at 1.3 V exhibits very limited dropout voltage and super-flat platform, with a remarkable capacity of 600 mAh g(-1) at 5 A g(-1) stable up to 6000 cycles, confirming that the polyiodide generation and storage are sustainable. The COF's dual-ion storage (Zn2+ and polyidode) delivers a ZIB with the highest energy density. Spectro-electrochemical measurements coupled with X-ray photoelectron spectroscopy unambiguously unveil the existence of multiple polyiodide species, with I-3(-) and IO3- ions as the prominent species. The latter gets reduced at the COF electrode under an applied potential, leaving I-3(-) as the major species stored on the COF. The prospect of COF-polyiodide((aq)) is a windfall for metal-ion batteries.
Keywords: covalent organic frameworks; flexible batteries; polyiodide; redox electrolytes; Zn ion batteries